Nickel-iron catalyst for decomposition of methane to hydrogen and filamentous carbon: Effect of calcination and reaction temperatures - Abdulrahman I. Alharthi (Alexandria Engineering Journal, 2023)
Nickel-ferrite Ni-Fe (molar ratio 1:2) were synthesised and calcined at different temperatures. The catalytic performances of Ni-Fe for methane decomposition and production of hydrogen and carbon nanostructures were evaluated at various calcination (350–800 °C) and reaction temperatures (700–800 °C). Fresh and spent catalysts were characterized using scanning electron microscopy (SEM), BET surface area, X-ray diffraction (XRD), TGA and Raman spectroscopy. XRD results revealed the formation of highly crystalline NiFe2O4 in calcined samples, while Ni-Fe alloys were observed in the spent catalysts. The NiFe2O4 catalyst has a mesoporous structure with monomodal pore distribution. The surface area decreased from 107.0 to 3.8 m2/g with increasing calcination temperature from 350 to 800 °C. Methane conversion, 48.50%, and hydrogen formation rate, 97.70 × 10-5 mol H2 g−1 min−1 was obtained at reaction temperature of 800 °C. The catalyst activity slightly improved by increasing calcination temperature. The SEM images of spent catalysts revealed the formation of some filamentous carbon over all spent catalysts except for that operated at reaction temperature of 700 °C. TGA studies revealed that the deposited carbon increased with increase in reaction and calcination temperatures and achieved 42.50 and 59.32 wt%, respectively. The graphitization and crystalline of the deposited carbon slightly decreases as calcination temperature increased.